Peach palm residue compost as substrate for Bactris gasipaes self-sustaining seedlings production - Francielen Paola de Sá; Andreza Cerioni Belniaki; Maristela Panobianco; Mônica Moreno Gabira; Dagma Kratz; Edson Alves de Lima; Ivar Wendling; Washington Luiz Esteves Magalhães (International Journal of Recycling of Organic Waste in Agriculture)
Purpose To comply with purposes of circular economy and sustainability, as well as promoting an appropriate destination for waste from Bactris gasipaes agro-industry and adding value to this product, we evaluated the compost of the plant residue as substrate for seedlings production. Methods Waste was collected, composted, dried and ground. Compost samples were characterized chemically and physically. The treatments consisted of different proportions of compost and soil (medium commonly used in B. gasipaes seedling nurseries), to make five growth media (v:v composted peach palm:soil): T1 - 100: 0; T2 - 75:25; T3 - 50:50; T4 - 25:75 and T5- 0: 100. After 120 days of planting the peach palm seedlings, morphological parameters were evaluated. Results  For the majority of physicochemical properties, T1 showed superior characteristics, i.e. higher water retention capacity (74.19 v/v), higher total porosity (74.78%) as well as higher concentrations of N, P, K (with 2.90 %, 3412.00 g dm-3 and 7120.00 g dm-3, respectively) when compared to T5. Likewise, for seedling morphological parameters, the material grown in T1 presented higher height and shoot fresh and dry weight. Conclusion  B. gasipaes residue compost shows adequate amounts of macro and micronutrients and physical properties that enable satisfactory development of seedlings from the species, thus promoting a self-sustainable seedling production system.